Guide to yeast genetics and molecular and cell biology. - Fink, Gerald R.; Guthrie, Christine (Methods in enzymology, 2002)
This volume and its companion, Volume 351, are specifically designed to meet the needs of graduate students and postdoctoral students as well as researchers, by providing all the up-to-date methods necessary to study genes in yeast. Procedures are included that enable newcomers to set up a yeast laboratory and to master basic manipulations. Relevant background and reference information given for procedures can be used as a guide to developing protocols in a number of disciplines. Specific topics addressed in this book include basic techniques, making mutants, genomics, and proteomics.